2017
DOI: 10.1111/joic.12458
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active cancer disease on the outcome of patients undergoing transcatheter aortic valve replacement

Abstract: The presence of ACD in patients undergoing TAVR is associated with significantly higher 1-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 29 publications
(55 reference statements)
0
51
3
Order By: Relevance
“…After screening the abstract from these articles, only 25 studies were eligible for full-text screening. In total, three studies16–18 (all observational) with a total of 5162 patients (368 patients (7.1%) with AC) were included in the final analysis (figure 1). The summary of the included studies and their main results are shown in table 1, the baseline characteristics of their populations are shown in table 2 and the cancer type distribution is shown in table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the abstract from these articles, only 25 studies were eligible for full-text screening. In total, three studies16–18 (all observational) with a total of 5162 patients (368 patients (7.1%) with AC) were included in the final analysis (figure 1). The summary of the included studies and their main results are shown in table 1, the baseline characteristics of their populations are shown in table 2 and the cancer type distribution is shown in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that data on TAVR outcomes in patients with or without AC are very few and heterogeneous (with some investigators reporting similar all-cause mortality rates16 at the 1-year follow-up while others did not),17 18 we conducted this systematic review and meta-analysis to provide information for improving the clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Preferred Reporting Items for Systemic Reviews and Meta-Analyses (PRISMA) ow chart of the study selection is shown in Figure 1. Major excluded articles [19,[34][35][36][37][38][39] with reasons are reported in the Supplemental Appendix. The 4 included studies enrolled a total of 2054 patients; 164 patients with prior C-XRT, and 1890 patients without prior C-XRT.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The difference in outcomes for patients with cancer and active disease versus those in remission was demonstrated recently in a registry that included 1821 subjects treated by TAVR [24]. Ninety-nine patients (5.4%) had different types of active cancer, while 251 patients had a history of treated cancers, currently in remission.…”
Section: Tavr In Cancer Patientsmentioning
confidence: 98%
“…The prevalence of cancer in patients with severe AS varies between 5.4 and 26% [24,28]. There are very few reports regarding the prognosis of patients with valvular disease and cancer, and even less are available in patients with AS.…”
Section: Aortic Stenosis Prevalence and Prognosis In Cancer Patientsmentioning
confidence: 99%